Comparative study between two fabricated potentiometric sensors to enhance selectivity towards ferrous ions. (16th July 2019) - Frag, Eman Yossri; Mohamed, Marwa El Badry; Mohamed, Gehad G.; Samy, Yasser
Abstract : Electroanalytical methods are highly selective for measuring electrical quantities including the charge, potential and current with their relation to chemical parameters. They are widely applied in various fields such as biochemical analysis, industrial quality control and environmental monitoring. They have many advantages over other techniques in that they are not time consuming and are specific for certain oxidation states of certain elements which give these techniques high selectivity and sensitivity features. This paper is based on two parts: the first part describes the fabrication of screen‐printed electrodes (SPEs) modified with methyl red as electroactive material, while second part describes the preparation and characterization of Fe(II)–methyl red complex using various spectroscopic tools, the complex being used for the construction of carbon paste electrodes (CPEs). The two proposed electrodes were successfully applied for the determination of Fe(II) in water and pharmaceutical (pharovit) samples. The electrodes under investigation show potentiometric response for Fe(II) in the concentration range 8.0 × 10 −7 –1.0 × 10 −2 and 5.0 × 10 −7 –1.0 × 10 −2 M at 25°C for SPE and CPE, respectively, and the electrode response is independent of pH in the range 1.5–7.0. These sensors show Nernstian slopes of 29.1 ± 0.2 and 29.7 ± 0.16 mV decade −1 with detection limit values of 8.0 × 10 −7 and 5.0 × 10 −7 M for SPE and CPE, respectively. These electrodes show fast response time of 6 and 4 s and exhibit a lifetime of 100 and 30 days for SPE and CPE, respectively. The mechanism of chemical reaction between modifier and Fe(II) on the SPE surface was studied using infrared spectra, scanning electron microscopy and energy‐dispersive X‐ray analysis. The proposed potentiometric method was validated according to the IUPAC recommendations. The results obtained using the proposed sensors were comparable with those obtained with inductively coupled plasma analysis. Abstract : The paper describes the fabrication of screen‐printed electrodes modified with methyl red as electroactive material and the preparation and characterization, using spectroscopic tools, of Fe(II)–methyl red complex which was used for the construction of carbon paste electrodes. The two proposed electrodes were successfully applied for the determination of Fe(II) in water and pharmaceutical (pharovit) samples.